[LETTER CONCERNING THE RECENTLY RECEIVED FIRE SENSE VIDEOS] (Tufts Archival Research Center, 2007)
Letter from the fire education specialist at the Newport News Fire Department to a representative of the Tobacco Institute. Praises the Fire Sense Videos and expresses plans to use them at a yearly fire safety conference. Thanks the Tobacco Institute for all of its support towards the Newport News Fire Department.